2019
DOI: 10.1177/0269216319870649
|View full text |Cite
|
Sign up to set email alerts
|

Does inpatient palliative care consultation impact outcomes following hospital discharge? A narrative systematic review

Abstract: Background: While most patients desire to die at home or in a community-based hospice, the transition from hospital to community settings often lacks streamlined coordination of care to ensure that adequate support is provided in the preferred care setting. The impact of hospital-based palliative care consultations on post-discharge care and outcomes has not been extensively studied. Aim: The aim of this study was to appraise available research on the impact of inpatient palliative care consultations on transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 47 publications
(194 reference statements)
1
29
0
1
Order By: Relevance
“…Several recently published meta-analyses and systematic reviews point to the significant role of palliative care interventions on enhancing quality of life and reducing symptoms burden and health care cost and utilization. [161][162][163][164][165][166][167] A systematic search of 124 randomized controlled trials shows that palliative care improves outcome of many end-of-life conditions including cancer, chronic heart failure, chronic obstructive pulmonary disease, and dementia. These systematic reviews point to the effectiveness of communication and psychosocial support.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recently published meta-analyses and systematic reviews point to the significant role of palliative care interventions on enhancing quality of life and reducing symptoms burden and health care cost and utilization. [161][162][163][164][165][166][167] A systematic search of 124 randomized controlled trials shows that palliative care improves outcome of many end-of-life conditions including cancer, chronic heart failure, chronic obstructive pulmonary disease, and dementia. These systematic reviews point to the effectiveness of communication and psychosocial support.…”
Section: Methodsmentioning
confidence: 99%
“…162 Moreover, reviews of current literature show that inpatient palliative care consultations have the potential to improve patient quality of life and encourage transitions to the community, thereby relieving overburdened acute care facilities. 165 Two other recent systematic reviews of palliative care for advanced heart failure patients reveal that palliative interventions substantially reduce hospitalizations, 163 improve patientcentered outcomes, documentation of preferences, and health care utilization. 164 Along the same line, another systematic review revealed that receiving palliative care was associated with lower emergency department attendance in the last year of life for older adults.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show a difference in the number of treated patients between urban and rural regions but no differences with respect to the continuity of palliative care. Readmission of patients after discharge from inpatients palliative care can be an indication of insufficient discharge management and a lack of support in the ambulatory health care setting [18]. Other possible risk factors for hospital readmissions within 30 days include neoplasms, prescribed opiates, comorbidities and an increased number of hospitalisations in the past [19].…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies show that inpatient palliative care is associated with reduced burdensome transitions, 3 reduced health service utilization and costs, 4 and increased likelihood of death in the preferred place. 5,6 This is not surprising, as planning for care after discharge to the home setting is a key component of inpatient palliative care delivery. 7 Discharge referrals from inpatient palliative consultations can initiate patients' entry into home health care programs, 8 making it a potentially useful bridge between acute and home care.…”
Section: Introductionmentioning
confidence: 99%